PRESENTATION OF PUBLICATIONS ON ISSUES OF THE GENERAL SECONDARY EDUCATION IN ABSTRACT DB "UKRAINIKA SCIENTIFIC" - Nataliia M. Kropocheva (Information technologies and learning tools, 2014)
In the article there are analyzed the abstracts of theses on general secondary education and training. The dynamics of the objects on the species, thematic, chronological and geographical features in the period 1998-2012 (based on abstract database "Ukrainika scientific") is analyzed. It was researched abstract information on defending the thesis for a candidate and doctorate degree on the following criteria: membership of a particular scientific field, the scientific profession, place of protection. Thesis is grounded on the presence of correlations number of abstracts of dissertations and regional association publications, most of which were produced in large administrative, scientific and cultural centers of Ukraine.